Role of central retinal artery and ophthalmic artery color doppler imaging in patients with increased intraocular pressure - Alka Agrawal; Gaurav Bhandari; Suhas Kattigowda; Mayank Patidar; Manzill JP (Journal of Preventive and Complementary Medicine)
Background: Glaucoma is a leading cause of irreversible blindness and involves complex multifactorial mechanisms, with vascular dysregulation playing a crucial role.Objectives: This study aimed to evaluate the utility of Color Doppler Imaging (CDI) in detecting early vascular changes in patients with elevated intraocular pressure (IOP) who do not exhibit detectable visual field defects.Methods: This cross-sectional study was conducted at MGM Medical College and MY Hospital, involving 100 patients divided into groups based on the presence or absence of visual field changes. CDI was utilized to assess the ophthalmic artery (OA) and central retinal artery (CRA) for peak systolic velocity (PSV), end-diastolic velocity (EDV), and resistivity index (RI). Statistical analysis was performed using SPSS, with significance set at p < 0.05.Results: Patients with visual field changes demonstrated significant reductions in PSV (OA: 33.5 cm/sec vs. 36 cm/sec; CRA: 14.5 cm/sec vs. 15 cm/sec) and EDV (OA: 7.5 cm/sec vs. 8.3 cm/sec; CRA: 4.3 cm/sec vs. 4.7 cm/sec) compared to those without visual field defects. Furthermore, the RI was increased in both the OA (0.79 vs. 0.77) and CRA (0.80 vs. 0.77), indicating early vascular dysfunction associated with disease progression.Conclusion: CDI serves as a non-invasive method for detecting vascular changes that precede visual field defects in glaucoma patients, highlighting its potential for early diagnosis and management. While the findings are promising, further longitudinal studies are necessary to validate its routine clinical application.